2018
DOI: 10.12816/0045841
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypothyroidism and Its Associated Risk Factors in Arar City, Saudi Arabia

Abstract: Background: Hypothyroidism is a common endocrine disorder worldwide. The prevalence of hypothyroidism depends on many factors, such as age, sex and geographical factors. Objective: This study is carried out to assess the prevalence of hypothyroidism and the related etiology and risks in the general population of Arar city, northern border of Saudi Arabia. Methods: A cross-sectional study was conducted in Arar, Northern Saudi Arabia. A multistage stratified random sampling technique was used. A pre-designed onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…In another study, Moussa et al reported that 175 patients, 98 (71 females and 27 males) had hypothyroidism [35]. Similarly, Alrowaili et al (2018) demonstrated that the prevalence of hypothyroidism was 25.5% and that the disease was more prevalent among females than males [38]. In general, females were found to be the majority of those with thyroid dysfunction in this study.…”
Section: Discussionsupporting
confidence: 61%
“…In another study, Moussa et al reported that 175 patients, 98 (71 females and 27 males) had hypothyroidism [35]. Similarly, Alrowaili et al (2018) demonstrated that the prevalence of hypothyroidism was 25.5% and that the disease was more prevalent among females than males [38]. In general, females were found to be the majority of those with thyroid dysfunction in this study.…”
Section: Discussionsupporting
confidence: 61%
“…This distribution aligns with the generally higher prevalence of hypothyroidism in females and an increased incidence observed with advancing age. Predominance of females and similar age patterns has been observed in other studies done by Alruwaili et al, 2018; Aljabri et al, 2019 and Alqahtani, 2021 [9,10,18]. However, in a study done by Senthilkumaran et al, 2015, they found that the majority of female participants were between the ages of 55 and 67 years [19].…”
Section: Demographic Distributionsupporting
confidence: 78%
“…Many of the risk factors highlighted are potentially modifiable, which emphasizes the importance of public health programs in tackling the disorder [7]. Alruwaili et al, 2018, in a study in Arar City, Saudi Arabia, observed that the prevalence of hypothyroidism was 25.5% and females (57.7%) were more affected than males and 40% of the cases had a positive family history [9]. Aljabri et al, 2019, observed that hypothyroidism was highly prevalent in a cohort of Saudis.…”
Section: Introductionmentioning
confidence: 99%
“…However, higher prevalence rates were reported in other studies in the kingdom exclusively in women. From Arar, a prevalence rate of 25.5% was reported in those aged 21-60 years old [ 9 ]. The highest prevalence (35%) was reported in those aged above 50 years [ 10 ] reflecting age as a contributing factor in elderly patients.…”
Section: Discussionmentioning
confidence: 99%